Oceanography Studies Stimulate the District Sustains Island Water District Meranti Islands in Riau Province - Bambang Supratman; Mubarak '; Musrifin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted on Date December 17, 2013 - December 31, 2013 in the waters of the island located in the District Augments Stimulation Meranti Islands Regency of Riau Province. Sustains Island coastal region is an area that is affected by tides and waves, where one result of the magnitude of wave and tidal current that goes to the beach cause some physical damage such as: land erosion (abrasion) in these coastal waters. The purpose of this study was to measure the speed and direction of currents, determine the type of tides, tidal currents describe Sustains Island waters, with the known velocity tidal currents, it can be seen that the damage resulted in changes in beach profile shape. The method used in this study is a survey method. On the island waters Sustains the above calculation, the average difference between the position of the high water and low water Sustains Island is 415.7 cm and the average position of the lowest water is 86.9 cm, high-elevation curves portray the sea water level. Type Sustains Island tidal tidal Sustains Island-type mix with prominent double type. Keywords: Water Sustains Island, Oceanographic Studies